b-1+6b=23

Simple and best practice solution for b-1+6b=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b-1+6b=23 equation:


Simplifying
b + -1 + 6b = 23

Reorder the terms:
-1 + b + 6b = 23

Combine like terms: b + 6b = 7b
-1 + 7b = 23

Solving
-1 + 7b = 23

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 7b = 23 + 1

Combine like terms: -1 + 1 = 0
0 + 7b = 23 + 1
7b = 23 + 1

Combine like terms: 23 + 1 = 24
7b = 24

Divide each side by '7'.
b = 3.428571429

Simplifying
b = 3.428571429

See similar equations:

| 0.99n+48y=c | | 31x+17y=364 | | 10x+24=114 | | -4x-15=12x-7 | | 4x+7-3x=9 | | 21x+20Y=570 | | 7(x+1)+4(2x-7)=6(2x+5) | | 60+(x+20)3x=180 | | 3.69/10=12c | | 18x-21=177 | | 2x+6=3(x-2) | | 4/5x+2=-1/5x+5 | | 7x+18x-9=5(5x+5) | | 4x-7=9x-5 | | 15x+60=165 | | 13.24-2.7p=5.5p-0.7 | | 5x+3.0=2x+3.3 | | 14+56=28w | | .66y+v=x | | 13x+84=175 | | 5n+72=3n-36 | | n-3=-n+3 | | 8a-2a= | | 9w=6.3 | | y=2/3(11)+4 | | -15=(5q-10)-5q | | 2(w-4)=26 | | (5y-7)^-4/3((5y-7)-3) | | 5x-22=3x+16 | | -1.5(x-2.25)=-10.55 | | -3p+4=-9(5p-10)-2(-5-5p) | | 1/8(a+3)=1/4(9-a) |

Equations solver categories